Implementasi Sensor Ultrasonik Dalam Mendeteksi Volume Limbah B3 Pada Tempat Sampah Berbasis Internet of Things - Febry Purnomo Aji; Arip Solehudin; Chaerur Rozikin (Department of Science and Technology Ibrahimy University, 2021)
In the process of monitoring the capacity of the B3 waste storage facility at PT Fadira Teknik, the manual method is still used to determine whether the waste load is full (ready to be disposed) or not. Where in the process, workers must come and look directly at the B3 waste storage area. This will increase jobs for factory workers because they must always monitor the level of B3 waste before or after carrying out work. Apart from being harmful to humans, the B3 waste disposed of from the factory is in the form of small particles such as invisible dust which can be accidentally inhaled by the nose or into the eyes of the workers. Therefore the aim of this research is to create a smart trash can system that can monitor the volume of B3 waste in the trash, where the trash uses the IoT (Internet of Things) system by utilizing the Arduino Uno component as a microcontroller and ultrasonic sensor to detect the volume of waste then sends waste volume data to the Blynk application via the internet network to display information on the capacity of the trash. The research method used is the experimental method starting from system analysis, system design, system implementation, testing and evaluation. Testing on this smart trash system uses black box testing with the results of these tests being quite good where each test case is as expected.